2014
DOI: 10.1177/1043454214554012
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Pediatric Cancer Survivors With Neurocognitive Late Effects

Abstract: Educational difficulties are common for childhood survivors of central nervous system (CNS) cancers. Children who have been treated for brain tumors and those who have received treatments involving the CNS are at increased risk of developing neurocognitive late effects including difficulties with attention, executive functioning, speed of processing, and academic functioning. These children are also at risk for difficulties with social functioning and social isolation. This hospital's School Liaison Program (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 13 publications
1
39
0
Order By: Relevance
“…Previous seminal work on school reentry that preceded the selected search timeframe was captured and synthesized in the meta‐analyses included in this review . Studies indicated that school reentry efforts, in their various formats, were well‐received, well‐accepted, and deemed helpful by parents and educators . In general, school reentry programs and approaches varied widely across studies but commonly targeted parents, school personnel, or the patient's classmates, rather than the patients themselves.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous seminal work on school reentry that preceded the selected search timeframe was captured and synthesized in the meta‐analyses included in this review . Studies indicated that school reentry efforts, in their various formats, were well‐received, well‐accepted, and deemed helpful by parents and educators . In general, school reentry programs and approaches varied widely across studies but commonly targeted parents, school personnel, or the patient's classmates, rather than the patients themselves.…”
Section: Resultsmentioning
confidence: 99%
“…Stakeholders reported that educators need to keep in touch with children as they recover, that parents and teachers must work together to facilitate a smooth transition back to school, and that support from teachers, tutors, and the hospital staff was instrumental in creating a positive school re‐entry experience . To support collaboration and address communication challenges, several reviewed studies suggest a designated team member (e.g., NP, school liaison) may be helpful …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…School visits can be very beneficial for both the patient and for the classroom, as they provide accurate information about cancer and its treatment, and dispel rumors or misconceptions that may be circulating (Northman et al, 2015).…”
Section: Active Treatmentmentioning
confidence: 99%
“…Regardless of risk factors, survivorship groups and treatment have been shown to be useful in coping and regaining functioning (Nathan et al, 2009). The study of school liaison programs have shown them to be highly valued and correlated with quicker and more successful returns to the school setting (Northman, Ross, Morris, & Tarquini, 2015;.…”
Section: End Of Treatmentmentioning
confidence: 99%